Perception of Salicylic Acid in Physcomitrella patens - Peng, Yujun; Sun, Tongjun; Zhang, Yuelin (Frontiers in Plant Science, 2017)
Salicylic acid (SA) is a key signaling molecule in plant immunity. Two types of SA receptors, NPR1 and NPR3/NPR4, were reported to be involved in the perception of SA in Arabidopsis. SA is also synthesized in the non-vascular moss Physcomitrella patens (P. patens) following pathogen infection. Sequence analysis revealed that there is only one NPR1/NPR3/NPR4-like protein in P. patens. This agrees with the phylogenetic study that showed the divergence of NPR1 and NPR3/NPR4 from the same ancestor during the evolution of higher plants. Intriguingly, expression of the P. patens NPR1/NPR3/NPR4-like gene in Arabidopsis does not complement the constitutive defense phenotype of the npr3 npr4 double mutant, but can partially rescue the mutant phenotypes of npr1-1, suggesting that it functions as an NPR1-like positive regulator of SA-mediated immunity and P. patens does not have an SA receptor functioning similarly as NPR3/NPR4. Future characterization of the P. patens NPR1-like protein and analysis of its functions through knockout and biochemical approaches will help us better understand how SA is perceived and what its functions are in P. patens.